Concervation Status of Caught Fish on the Coast Pangandaran, Pangandaran District, West Java - Kamiswara, Rendika; Herawati, Titin; Nurhayati, Atikah; Yustiati, Ayi (Jurnal Perikanan Universitas Gadjah Mada, 2024)
Pangandaran has high potential in the tourism and fisheries sectors. Marine resources that are open access and can be used by anyone cause the sustainability of resources to be threatened due to over-exploitation. Traditional fishermen are one of the livelihoods owned by the majority of coastal communities, especially in the Pangandaran Coastal area. However, fishing activities have not been carried out wisely, and become a threat to the sustainability of sustainable marine biota. Small fishermen get by-catch in the form of protected marine life and are included in the IUCN Red List and the CITES Appendix list. This research was conducted to find out the species of marine biota with important conservation status or included in the status of the IUCN red list and the CITES Appendix list caught and traded in the coastal areas of Pangandaran Regency. The research was conducted using field observation method with purposive sampling technique in 2 locations; the east coast and the west coast of Pangandaran. There are 47 fish species found in all research sites with conservation status not evaluated (12.8%), least concern (83.0%), near threatened (2.1%), vulnerable (2.1%), and included in CITES Appendix II (2.1%).